Flow and heat transfer investigation of forced convection of nanofluid in a wavy channel at different wavelengths and phase difference - Esmaeil Abokazempour; Abbas Ramiar; Ali Akbar Ranjbar; Majid Rahgoshay; Amir Arya; Mazaher Rahimi Esbo (Boletim da Sociedade Paranaense de Matemática, 2018)
Changing the fluid properties and flow geometry are two common ways of making an improvement in heat transfer rate. Recent investigations on nanofluid, as such suspensions are often called, indicate that the suspended nanoparticles remarkably change the transport properties and heat transfer characteristics of the suspension. Bending walls can also improve heat transfer by increasing the total heat transfer surface and changing the behavior of the flow. In this work a two dimensional incompressible laminar nanofluid flow in a wavy channel with sinusoidal curved walls is numerically investigated. The finite volume method, and Rhie and Chow interpolation with a collocated mesh are used for solving the governing equations. The effects of the volume fraction of nanoparticles, Reynolds number, the wavelength, Phase lag and amplitude on the heat transfer rate are studied. The present work showed good agreement with existing experimental and Numerical results. Increasing the amplitude of the wave and nanoparticles volume fraction, and decreasing wavelength of the wave, has great effects on enhancement of heat transfer rate.